SIMULATION AND ANALYSYS OF HYDRATE FORMATION POTENTIAL OF CITY GAS PIPELINE SYSTEM - Susilowati, Dian
City gas is one of government’s program in order to reduce fuel subsidies, especially kerosene and/or LPG household sector consumption through The Ministry of Energy and Mineral Resource. City gas is natural gas which is distributed to households by multy stages pressure reducing. Siginificant depressiurization raise hydrate formation. First depressurization, natural gas 73 Barg will be reduce to 16 Barg through The Pressure Regulating System (PRS) unit. The second stage depressurization is 16 Barg to 4 Barg in Metering & Regulating Station (MRS) Unit. The next depressurization stage is 4 Barg to 0.5 Barg which occurs at the Regulator Station (RS). The last depressurization stage is gas from the distribution pipe of 0.5 Barg through the household regulator so that the pressure becomes 35 mbarg. This thesis has purpose to analyze the probability of hydrate formation due to significant pressure depressurization. ASPEN HYSYS V.10 software will be used as tool to make hydrates formation modelling curve and analyze hydrate formation operation condition. From the modelling result under normal condition, Outlet temperature of PRS, MRS and RS are 6.98 oC; 5.50 oC and 23.37 oC respectively. Hydrate formation temperature are -27.64 oC for PRS, -36.40 oC for RS and -49.94 oC for RS. This result shows that operation temperature is above hydrate formation temperature and in safe operation condition. Simulation in variant variable i.e flow rate, temperature and pressure of feed gas,Outlet pressure of MRS and RS. All variant simulations from minimal until maximal condition is above hydrate formation temperature area. Conclution for this simulation is pipeline system for city gas doesnt need any method for prevention of hydrate formation.